Sum pattern

*To*: mathgroup at smc.vnet.net*Subject*: [mg128268] Sum pattern*From*: "Dave Snead" <dsnead6 at charter.net>*Date*: Wed, 3 Oct 2012 03:07:29 -0400 (EDT)*Delivered-to*: l-mathgroup@mail-archive0.wolfram.com*Delivered-to*: l-mathgroup@wolfram.com*Delivered-to*: mathgroup-newout@smc.vnet.net*Delivered-to*: mathgroup-newsend@smc.vnet.net*References*: <20120930000917.61B1A6865@smc.vnet.net>

Hi, I'm trying to put together a rule whose left hand side is a sum of arbitrary length whose elements all have the same head f. For example: In[4]:= x = f[a1, s] + f[a2, s] + f[a3, s] Out[4]= f[a1, s] + f[a2, s] + f[a3, s] In[6]:= y = f[First /@ x, s] Out[6]= f[a1 + a2 + a3, s] which is what I want. However when I turn this into a rule In[7]:= z = x /. (p : Plus[__f]) -> f[First /@ p, s] Out[7]= f[f[a1, s], s] + f[f[a2, s], s] + f[f[a3, s], s] Why isn't z equal to y? How can I make this rule work? Thanks in advance, Dave Snead